Efektifitas Model Pembelajaran Inquiry Based Learning dalam Meningkatkan Pembelajaran Bahasa Indonesia Siswa SMP Kecamatan Sabbangparu - Sri Wahyuni; Arisa Arisa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
This study aims to discuss the effectiveness of learning inquiry based learning model in improving the learning of Indonesian junior high school students in Sabbangparu District. The data collected in this study, carried out through two cycles. Research subjects were teachers and students of class VIII with a total of 32 students, consisting of 20 males and 12 females. The result of learning analysis after applied inkuiri model in class student of SMP Negeri 2 Sabbangparu Wajo Regency that is at student prasiklus stage which complete with value more than 75 counted 0 student with percentage of 100 percent unfinished. In the first cycle, the students learning achievement increased, that is 20 students with 63 percent complete percentage of study with a value of more than 75. In cycle II also an increase that is a complete student with a value of more than 75 as many as 28 students with 88 percentage. So complete students learn to increase from 68 percent to 88 percent. Based on the results of the research, it can be concluded that the application of inquiry model effectively improves the learning of Indonesian junior high school students in Sabbangparu subdistrict, especially on the matter of writing argumentation text. After the existence of the research, it is suggested that teachers should always supervise the class to motivate students' activeness and provide individual and group guidance. Keywords: Effectiveness, Inquiry, Students, Sabbangparu